Rehabilitation of atrophic mandible with implants. Strategy and case report of fracture complication (Research, Society and Development, 2020)
Rehabilitation through implant-supported prosthesis on atrophic jaws presents great deal of difficulty. Mandible fractures related to implants is not a common complication, however when it occurs, it represents serious damage. The aim of this paper was to report a clinical case of a 63-year-old patient with mandibular fracture after implant installation, treated through a buccal access and load-shearing plate system to stabilize the fractured bone and reduce the discomfort. The use of load shearing plate presented good results in this case, stabilizing the bone fracture, and helping with the repairing process, enabling subsequent rehabilitation of the patient, with a 3-year follow-up.